Application of Legal Sanctions Against Perpetrators of Social Media Account Theft Based on the Law on Information and Electronic Transactions - Marsa Zahirah Badzlin; Kayla Putri Adnin; Jose Mikha Sembiring; Jessica Cristiana Siahaan; Suci Ramadani (International Forum of Researchers and Lecturers, 2026)
The swift advancement of information technology has greatly influenced society, while also raising the threat of cybercrime. These offenses encompass the theft of social media accounts, unauthorized access to online information, and breaches of personal data security. This research intends to explore various types of cybercrime in Indonesia, the legal measures in place, and the obstacles law enforcement encounters when proving cybercrime incidents. The study adopts a qualitative method by reviewing literature, which includes laws, court rulings, academic articles, and reports from pertinent organizations. The findings reveal that even though laws like the Electronic Information and Transactions Law and the Personal Data Protection Law establish a legal framework, there are still issues related to digital evidence, coordination between agencies, and the public's understanding of data security. Consequently, there is a need for a more thorough law enforcement approach, enhanced digital education, and collaborative efforts among the government, law enforcement agencies, and the community to effectively combat and manage cybercrime.